Biotechnology for sustainable development. - Clark, Norman (1991)
Shows that biotechnology offers new opportunities for diversifying economic activity for dealing with persistent environmental problems and for improving living conditions of Third World populations. Also notes that biotechnology poses major risks to society and the environment and that its benefits cannot be ensured without deliberate efforts to shape its development.